Chat with our AI personalities
4a*2c=8ac
12-2c = 2c add 2c to both sides 12 = 4c divide both sides by 4 3 = c
8e4 / -4r3 = (2 x 4)e x e3 / -4r3 = -2e (e/r)3
var(x) = E[(x - E(x))2] = E[(x - E(x)) (x - E(x))] <-------------Expand into brackets = E[x2 - xE(x) - xE(x) + (E(x))2] <---Simplify = E[x2 - 2xE(x) + (E(x))2] = E(x2) + E[-2xE(x)] + E[(E(x))2] = E(x2) - 2E[xE(x)] + E[(E(x))2] <---Bring (-2) constant outside = E(x2) - 2E(x)E[E(x)] + E[(E(x))2] <--- E[xE(x)] = E(x)E(x) = E(x2) - 2E(x)E(x) + [E(x)]2 <----------E[E(x)] = E(x) = E(x2) - 2[E(x)]2 + [E(x)]2 var(x) = E(x2) - [E(x)]2
1-2c = -1